Poliomyelitis in the City of Córdoba: Morbidity, Knowledge and the Research Performed by a Medical Elite in Argentinas Interior, 1943-1953 - Carbonetti, Adrian (2015)
Our article will interrogate the connections between local medical science and knowledge produced in leading European countries, particularly in Sweden, and the United States. It will consider the kind of articles that were published in Córdoba, the sort of research was conducted there, and the link between knowledge produced elsewhere and local variables associated with the development of poliomyelitis. It should be understood that the receptive attitude displayed by members of the local medical community in Córdoba is closely linked to the sporadic appearance of fatal polio cases in the region from 1943 to 1952: the yearly totals of deaths attributed to this condition varied from year to year until the outbreak of an epidemic in 1952. This article will also comment on the city?s experience with massive immunization, both with the Salk vaccine, which contained killed viruses, and with the more efficient Sabin vaccine of 1963, both of which were, of course, named for eminent American scientists whose discoveries led to the initiation of the controlled phase of this disease epidemic. However, this article will not lose sight of the fact that although the biomedical science developed in Argentina was, from the nation?s founding, influenced by European scientists and European scientific discoveries, the processes by which this knowledge was received cannot be considered static. Our reading of these events holds that, along with the production dynamic of knowledge relating to poliomyelitis, other processes for the acquisition of knowledge were also emerging at this time at the local level. These processes are noteworthy because they involved investigative strategies that raised questions about a number of social issues, including some related to mortality, in an environment that would prove important to the study and development of medical science.